GPU acceleration of the boundary element method for shear-deformable bending of plates. (January 2017) - Torky, Ahmed A.; Rashed, Youssef F.
Abstract: This paper presents a novel implementation of GPU computing for boundary element method (BEM) formulation of plates. The new GPU code written in CUDA Fortran alters three kernels: the calculation of influence matrices, the solution of equations, and the computation of internal values. Comparisons for computation time and different GPU architecture are presented. The formulation is implemented for both constant and quadratic elements. The efficiency of the parallel quadratic code is demonstrated via analysis of practical building slabs. The benefits of parallel computing of the solution of the system of equations and of points inside the domain are discussed. Highlights: Parallel approaches to constant and quadratic BEM plate bending problems. Comprehensive evaluation of computing time for constant GPU algorithms. A comparison between different GPU architectures for the same BEM codes. A proficient proposition for the development of practical quadratic GPU algorithms. A demonstration of genuine structural engineering problems solutions speed.